2013
DOI: 10.1021/cb4006408
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Transglutaminase 2 Activity Is Associated with Hypoxia-Induced Experimental Pulmonary Hypertension in Mice

Abstract: Previous studies in human patients and animal models have suggested that transglutaminase 2 (TG2) is upregulated in pulmonary hypertension (PH), a phenomenon that appears to be associated with the effects of serotonin (5-hydroxytryptamine; 5-HT) in this disease. Using chemical tools to interrogate and inhibit TG2 activity in vivo, we have shown that pulmonary TG2 undergoes marked post-translational activation in a mouse model of hypoxia-induced PH. We have also identified irreversible fluorinated TG2 inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(106 citation statements)
references
References 46 publications
9
94
3
Order By: Relevance
“…Our own studies have shown elevated serotonylated fibronectin in the serum of PAH patients and in animal models of pulmonary hypertension that we have linked to TG2 [17]. Moreover, the TG2 inhibitor ERW1041E mitigates pulmonary hypertension in a rodent model [18]. Furthermore, our recent findings indicate that TG2 contributes to hypoxia-induced pulmonary vascular smooth muscle cell mitogenesis (Penumatsa et al in press).…”
Section: Introductionmentioning
confidence: 89%
“…Our own studies have shown elevated serotonylated fibronectin in the serum of PAH patients and in animal models of pulmonary hypertension that we have linked to TG2 [17]. Moreover, the TG2 inhibitor ERW1041E mitigates pulmonary hypertension in a rodent model [18]. Furthermore, our recent findings indicate that TG2 contributes to hypoxia-induced pulmonary vascular smooth muscle cell mitogenesis (Penumatsa et al in press).…”
Section: Introductionmentioning
confidence: 89%
“…During polarization, the cells were incubated with 50 M NP161 or vehicle in the absence or presence of 200 M 5-biotinamidopentylamine, which was synthesized as described previously (34). The cells were washed in PBS, fixed for 5 min in 2% paraformaldehyde, and blocked overnight with 5% bovine serum albumin in PBS, pH 7.4, at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Next, we evaluated TG2 activity in M0 and M1 macrophages using an established assay to measure the incorporation of 5-biotinamidopentylamine (5-BP), a small molecule TG2 activity probe (7,34). TG2 activity positively correlated with TRX secretion, because 5-BP incorporation was elevated in M1 macrophages relative to M0 macrophages (Fig.…”
Section: Tg2 Activity In Macrophages Is Mediated By Endogenousmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps the most extensively evaluated are the weakly electrophilic 3-bromo-4,5-dihydroisoxazole class of inhibitors [74-81]. In vivo experiments using a prototypical inhibitor ERW1041E blocked elevated TG2 activity in pulmonary tissue in a mouse model of pulmonary hypertension [82]. In the same study, twice-daily intraperitoneal dosing of this inhibitor at 50 mg/kg was well tolerated over the course of several weeks.…”
Section: Preclinical Targetsmentioning
confidence: 99%